Detection of methicillin resistance of Staphylococcus aureus in vitreous humor using MALDI-TOF MS and Fc-MBL@Fe3O4 enrichment - Jun Ren; Wenjing Gao; Menghuan Yu; Chunhong Liu; Chuanfan Ding; Shengjie Li; Shaoning Yu; Wenjun Cao (Scientific Reports, 2024)
Abstract Endophthalmitis is a serious infectious eye disease that causes permanent vision loss. This study developed a method for rapid identification and drug resistance analysis of pathogens in vitreous humor. After short-term rapid culture, 30 Staphylococcus aureus isolates were enriched and purified from the vitreous humor using Fc-MBL@Fe3O4, and then identified by MALDI-TOF MS. The bacterial solution was adjusted to 106 CFU/mL and mixed with CAMHB containing cefoxitin (4 µg/mL) at the same volume. After culture, it was enriched by Fc-MBL@Fe3O4 and identified by MALDI-TOF MS. MRSA was judged according to whether the bacteria could successfully be identified. The enrichment efficiency of Fc-MBL@Fe3O4 for S. aureus in CAMHB was 88.1%. The detection rate of S. aureus reached 100% after 8 h of vitreous humor culture. The best test performance was achieved with Fc-MBL@Fe3O4 enrichment after a 3 h incubation. At this time point, 96.7% validity, 100% sensitivity, and 100% specificity were achieved. Thus, the identification and drug resistance analysis of S. aureus (51–110 CFU) in vitreous humor was completed within 11 h. This study provides a new method for rapid clinical diagnosis of endophthalmitis and precise treatment with antibiotics.